Germination and salinity tolerance of seeds of sixteen Fabaceae species in Thailand for reclamation of salt-affected lands - Yongkriat KU-OR; Nisa Leksungnoen; Damrongvudhi Onwimon; Peerapat Doomnil (Society for Indonesian Biodiversity, 2020)
Abstract. Ku-Or Y, Leksungnoen N, Onwinom D, Doomnil P. 2020. Germination and salinity tolerance of seeds of sixteen Fabaceae species in Thailand for reclamation of salt-affected lands. Biodiversitas 21: 2188-2200. Over the years, areas affected by salinity have increased dramatically in Thailand, resulting in an urgent need for reclamation of salt-affected areas using salinity tolerant plant species. In this context, seed germination is an important process in plant reproduction and dispersion. This research aimed to study the ability of 16 fabaceous species to germinate and tolerate salt concentrations of at 6 different levels (concentration of sodium chloride solution, i.e., 0, 8, 16, 24, 32, and 40 dS m-1). The germination test was conducted daily for 30 days, and parameters such as germination percentage, germination speed, and germination synchrony were calculated. The electrical conductivity (EC50) was used to compare the salt-tolerant ability among the 16 species. Our results showed that the germination percentage, germination speed, and germination synchrony of all species decreased with an increase in salinity concentration. The mean germination time increased from 2-4 days under 0 dS m-1 to 4-10 days under 16 dS m-1, indicating that the seeds germinated at a slower rate as the salinity levels increased. Seed germination percentage was more than 80% across all the species at salinity levels between 0 to 16 dS m-1. Sesbania grandiflora, Senna siamea, and Dalbergia cochinchinensis had a high EC50 value of 33.56, 32.93, and 30.83 dS m-1 respectively, suggesting that these species were the three most salt-tolerant species in this study. As such, the establishment of these species in salt-affected areas should be studied further in order to reclaim such affected lands.